The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0018720820941618
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lateral Auditory Collision Warnings: Should Warnings Be Toward Danger or Toward Safety?

Abstract: Objective The present study investigated the design of spatially oriented auditory collision-warning signals to facilitate drivers’ responses to potential collisions. Background Prior studies on collision warnings have mostly focused on manual driving. It is necessary to examine the design of collision warnings for safe takeover actions in semi-autonomous driving. Method In a video-based semi-autonomous driving scenario, participants responded to pedestrians walking across the road, with a warning tone present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
6
1
Order By: Relevance
“…Nonetheless, ipsilateral warnings led to higher self-reported satisfaction than contralateral warnings. Previous research has found faster response times for ipsilateral warnings [23] (see [24] for vibrotactile warnings) than for contralateral warnings, or vice versa [18,26] or has suggested that time budget is a crucial moderator variable [25]. Our null result can be interpreted in the context of previous papers that have indicated that the phenomenon of spatial multisensory synergy is highly task-dependent [9].…”
Section: Ipsilateral Vs Contralateral Warningscontrasting
confidence: 40%
See 3 more Smart Citations
“…Nonetheless, ipsilateral warnings led to higher self-reported satisfaction than contralateral warnings. Previous research has found faster response times for ipsilateral warnings [23] (see [24] for vibrotactile warnings) than for contralateral warnings, or vice versa [18,26] or has suggested that time budget is a crucial moderator variable [25]. Our null result can be interpreted in the context of previous papers that have indicated that the phenomenon of spatial multisensory synergy is highly task-dependent [9].…”
Section: Ipsilateral Vs Contralateral Warningscontrasting
confidence: 40%
“…When a warning is provided early, on the other hand, a contralateral warning will lead to a faster response because it attracts visual attention towards the hazard (see also [18]). More recently, Chen et al [26] investigated spatial pedestrian collision warnings for time budgets between 2 and 4 s and found that participants responded faster to contralateral than ipsilateral warnings for all time budgets. No advantage of ipsilateral warnings was found for short time budgets, which is inconsistent with Straughn et al's findings.…”
Section: Ipsilateral Versus Contralateral Warningsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to this undeniable subjectivity, even though duly quali ed, there is the need of applying analytical procedures for quantifying the users' performance, in real conditions representing the analysed scenario, often not predictable by road standards. In the recent past, with the progress of vehicle on board sensors, the estimation of the driving behaviour performance was entrusted to some indices able to synthetize the performance on a homogeneous element of the road that, preferably, was the horizontal curve (Chen et al, 2022;He & Donmez, 2022). At this regard, one of the most used variables in the scienti c research was the Lateral Position (LP), as the trajectory in curve directly in uences the values of the lateral acceleration and steering and, in turn, the manoeuvre safety.…”
Section: Introductionmentioning
confidence: 99%